Implementasi Open Banking Dalam Transformasi Digital Perbankan Di Indonesia: Studi Literatur - Gustiara, Gita; Nursitta Fathya, Nabila; Indah Lestari, Novia (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The implementation of Open Banking is a strategic step in accelerating the digital transformation of banking in Indonesia through the secure and standardized exchange of financial data between banks and third parties, particularly fintech companies. This implementation encourages more efficient and competitive financial service innovation, but also faces challenges such as data security risks, infrastructure readiness, and the need for strong regulations. This study aims to examine the role of Open Banking in the digital transformation of banking in Indonesia using a qualitative descriptive literature review method. The results of the study show that Open Banking plays an important role in driving digital transformation through collaboration between banks and fintech, with success highly dependent on regulatory readiness, information technology risk management, and customer data protection.